Estudos sobre morfometria de frutos e sementes, emergência de plântulas e crescimento inicial de mudas de mofumbo (Combretum leprosum Mart.) - Paulino, Renan da Cruz (2011)
The mofumbo (Combretum leprosum Mart.) is a plant used for beekeeping, popular medicine, and fodder. It also has great potential for the recovery of degraded areas, especially for its resistance to burns and cuts. Three different studies were performed with the aim of characterize fruits, seeds, seedlings, germination and emergence, growth and ecophysiology. EXPERIMENT I: Characterization of fruits, seeds and seedlings germination and biometry of Combretum leprosum Mart. (mofumbo) Combretaceae. Fruits and seeds biometrics were performed using a digital pachymeter; weight of 1,000 fruits and 1,000 seeds in a semianalytical balance; moisture content of seeds using the oven method at 105±3ºC for 24 hours; 100 seeds were germinated in germination trays with coconut fiber to describe germination and perform images. The unit of dispersal is the fruit, dry, indehiscent, brown type betulidio; one seed per fruit. The seed is monospermic with four longitudinal grooves; a thousand seeds weigh 117.3g with 11.5% of moisture. Germination is hypogeal cryptocotylar with storage cotyledons. Protophilus and metafiles differ in phyllotaxis. EXPERIMENT II: Seedling emergence of Combretum leprosum Mart. from different points in Mossoro, State of Rio Grande do Norte, Brazil. The experiment was conducted in order to verify whether there are differences in the vigor of seeds from different origins. The experimental design was completely randomized with five treatments(origins) with 5 replications per treatment, 40 seeds per experimental unit. The results were subjected to analysis of variance. The Tukey test at 5% was used to compare the means. The Pearson correlation coefficient was used to identify characteristics of the seeds and seedlings. Seeds with larger diameter and greater mass originated more vigorous seedlings, however they did not show higher number of emerged seedlings. The percentage of emergence and emergence rate index varied among seed lots. EXPERIMENT III: Initial growth and ecophysiology of mufumbo (Combretum leprosum Mart.) under different lighting. It was performed 5 assessments every 10 days. The growth rate was determined based on the leaf area and dry mass. Also, chlorophyll, stomatal conductance and photosynthesis measurements were made. It was observed high morphophysiological plasticity of the Combretum leprosum seedlings, with better development in less shaded environments